Rekonstruksi Pembelajaran Pendidikan Agama Islam Berbasis Artificial Intelligence dalam Perspektif Pendidikan Islam Kontemporer - Saiyidah, Luthfia Hanifatus; Sutriani, Ikat; Zulkarnain, Muadz Haidar; Muflikhatun, Muflikhatun; Kholid, Idham; Ayu, Sovia Mas; Mujib, Mujib (Paedagogie, 2026)
The development of digital technology, particularly Artificial Intelligence (AI), has brought significant changes in the field of education. However, Islamic Religious Education (PAI) learning still tends to be oriented toward a cognitive approach and has not optimally integrated technology in a substantive manner. This study aims to analyze and reconstruct the concept of AI-based PAI learning from the perspective of contemporary Islamic education. The method used is a library research approach with content analysis techniques applied to various relevant scientific literatures. The findings indicate that the utilization of AI in PAI learning has the potential to enhance learning effectiveness, personalize instructional materials, and strengthen students’ reflective capacities. Nevertheless, a paradigm reconstruction is required so that the use of AI is not merely technical but also capable of internalizing Islamic values. Therefore, the integration of AI in PAI learning should be directed toward the balanced development of cognitive, affective, and spiritual aspects.